CONTROL OF AGGLOMERATE DISTRIBUTION BY LAYER HEIGHT ON THE AGGLOMERATING CONVEYOR UNDER DIFFERENT LOADING CONDITIONS - Ovchynnykova, Iryna; Paziuk, Mikhailo; Barishenko, Olena; Kovalenko, Viktor (Scientific Journal "Metallurgy", 2024)
The article addresses the issue of managing the distribution of agglomerate charge by the height of the layer on the agglomerating conveyor during its loading. It is noted that the segregation of material particles affects key parameters such as gas permeability and fuel distribution within the layer. The task of solving this problem is formulated as finding the distribution of size classes of agglomerate charge by the height of the layer without segregation. The article utilizes models described in other studies to determine the distribution of size classes by the height of the agglomerate charge layer. The model is calibrated based on experimental data and loading device parameters. Calculation results for specific enterprises confirm the adequacy of the model, where the modeling error does not exceed 5.1%. The research also highlights the influence of loading device parameters and properties of the agglomerate charge on the distribution of fractions by height. Changes in the average particle diameter, tilt angle, and length of the loading chute affect segregation within the layer. Modeling results indicate that altering the average particle diameter significantly impacts the distribution of size classes in the agglomerate charge. The article addresses the challenge of managing the structure of the agglomerate charge layer on the agglomerating conveyor by altering loading device parameters, particularly the tilt angle. Results suggest the effectiveness of changing the tilt angle to control particle segregation.